Experimental and numerical analysis of electronics heat sink - Ismail, Ahmad Faris; Ahmed, Mirghani Ishak; Abakrb, Yousif A. (IIUM Press, 2002)
Cooling of electronic components continues to attract many research and development activities towards achieving an effective way of cooling. Computational fluid dynamics (CFD) tools may be considered as a cheap substitute for expensive experimental testing methods. In this work the cooling of a simulated electronic board was modeled using FLUENTTM CFD software, and experimental procedures were followed to validate the estimated results, and to understand the factors that would affect the software capability to predict the actual measured values. Results showed good agreement between the simulation and experimental results. The software was found to be capable to predict the exact values at the locations where the temperature values were similar to the board mean temperature. The maximum percentage error was found to be limited to 4.7%, and the capability of the software to estimate the exact measured values was found to be affected by the function of thermal wake generation.